Dosimetric Comparison between 6MV Flattened Filter and Flattening Filter Free Photon Beams in the Treatment of Glioblastoma with IMRT Technique: A Treatment Planning Study - Dinesh Saroj (Iranian Journal of Medical Physics, 2020)
Introduction: The present study evaluated the dosimetric comparison between 6MV flattened filter (FF) and flattening filter-free (FFF) photon beams in intensity-modulated radiation therapy (IMRT) technique for the treatment of glioblastoma (GBM) patients. Material and Methods: The present study was conducted on 10 patients with GBM previously planned and treated with 6MV FF photon beam by IMRT technique. Additional IMRT plans were retrospectively created using 6MV FFF photon beam for each patient plan. The dose prescription, beam parameters, and planning objective were kept same in both plans. The plans were evaluated using cumulative dose-volume histogram (c-DVH). Both types of plans were compared on the basis of homogeneity index (HI), conformity index (CI), beam-on time (BOT), monitor unit (MU), and doses to organs at risk (OARs). Results: Dose received by 95% (D95%) of planning target volume (PTV) coverage was observed significantly higher in 6MV_FF_IMRT plan than 6MV_FFF_IMRT plan (P<0.05). No significant dose differences were noticed for HI, CI, D98%, and D2% between both plans. Significantly lower Dmax for the brainstem, eyes, and eye lens was observed in 6MV_FFF_IMRT plan. For the brain, less than 2% mean dose was observed in 6MV_FFF_IMRT plan than 6MV_FF_IMRT plan (P=0.017). In 6MV_FFF_IMRT plan, mean BOT decreased by 39% in comparison to that in 6MV_FF_IMRT plans. Conclusion: The 6MV FFF beam provides a desirable and clinically acceptable IMRT plan for the treatment of GBM than 6MV FF beam. In addition, 6MV FFF beam provides higher MUs, better OARs sparing, lower scattered dose, and lower beam delivery time.